2019
DOI: 10.24106/kefdergi.3008
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğretmenlerinin Algılarına Göre Okul Etkililiği ile Kolaylaştırıcı Okul Yapısı ve Akademik İyimserlik Arasındaki İlişki

Abstract: Bu araştırmanın amacı ortaokul öğretmenlerinin kolaylaştırıcı okul yapısı, akademik iyimserlik ve okul etkililiği algıları arasındaki ilişkileri inceleyerek, öğretmenlerin kolaylaştırıcı okul yapısı ve akademik iyimserlik algılarının okul etkililiği algıları üzerindeki yordayıcılık etkisini belirlemektir. Katılımcılar; 589'u kadın ve 562'si erkek olmak üzere 1151 ortaokul öğretmeninden oluşmaktadır. Araştırma ilişkisel tarama modelinin kullanıldığı nicel bir araştırmadır. Araştırma sonuçlarına göre öğretmenler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
4
0
3
Order By: Relevance
“…This finding indicated that the coercive bureaucracy was experienced at a low level and the enabling bureaucracy structure at a high level. In this sense, collaborative management style (Alanoğlu & Demirtaş, 2020), organizational citizenship behaviors (Alev, 2019;Messick, 2012), job satisfaction (Bozkuş, Karacabey & Özdere, 2019), the effectiveness of management processes, positivist management, management approach (Sertel, Karataş, & Karadağ, 2021), supportive leadership (Özer, 2010), education-training, adaptability and flexibility (Çalık & Tepe, 2019), which positively affects the enabling bureaucracy, can be observed at high levels in organizations where the level of enabling bureaucracy is high.…”
Section: Findings Discussion and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding indicated that the coercive bureaucracy was experienced at a low level and the enabling bureaucracy structure at a high level. In this sense, collaborative management style (Alanoğlu & Demirtaş, 2020), organizational citizenship behaviors (Alev, 2019;Messick, 2012), job satisfaction (Bozkuş, Karacabey & Özdere, 2019), the effectiveness of management processes, positivist management, management approach (Sertel, Karataş, & Karadağ, 2021), supportive leadership (Özer, 2010), education-training, adaptability and flexibility (Çalık & Tepe, 2019), which positively affects the enabling bureaucracy, can be observed at high levels in organizations where the level of enabling bureaucracy is high.…”
Section: Findings Discussion and Resultsmentioning
confidence: 99%
“…Bu bulgular, örgütsel değişim ve kolaylaştırıcı bürokrasi arasındaki pozitif ilişkiyi destekler niteliktedir. Eğitim-öğretim ile kolaylaştırıcı bürokrasi (Çalık & Tepe, 2019) ve örgütsel değişim (Dönder Çelik, 1996) arasında pozitif ilişki saptanmıştır. Bu sonuçlar örgütsel değişim ve kolaylaştırıcı bürokrasi arasındaki pozitif ilişkiyi desteklemektedir.…”
Section: Tartişma Ve Sonuçunclassified
See 1 more Smart Citation
“…Bu nedenle iki farklı sosyo ekonomik çevrede çalışan öğretmenlerin benzer kodları vurgulaması doğaldır. Öğretmenlerin, okul yapısı ve akademik iyimserlik algılarının, okul etkililiği algıları üzerinde anlamlı bir yordayıcı olduğu araştırmaların gösterdiği bir gerçektir (Atış, 2020;Çalık & Tepe, 2019). Yani öğretmenin, öğrenme isteği duyan ve okula bağlı öğrencilerin bulunduğu okullardaki iyimser havadan olumlu etkilenmesi ve motive olması beklenir.…”
Section: Tartişma Ve Sonuçunclassified
“…According to the researchers, the starting point in SE should be instructional effectiveness. It can also be claimed that a facilitating organization structure, academic optimism, an appropriate culture, and a healthy school climate are essential components of SE (Calik & Tepe, 2019;MacNeil, Prater, & Busch, 2009;Senel & Buluc, 2016;Yavuz Tabak, Sahin & Tabak, 2018).…”
Section: Introductionmentioning
confidence: 99%